Filosofía, Religión y Compromiso ético - Carrasquilla, Jesús (2023)
This article is based on the line of argument that in Kant there is a bold and original interpretation of religion, which is made from a clearly philosophical hermeneutic viewpoint. This will have precise consequences on the ethical commitment of every human being, and the interactions that can be established between philosophy, religion, theology and human sciences in general. Kant’s perspective is marked by Pietism, and his particular reading of the Bible, and in this sense there is also conjecture that its interpretation is full of nuances and is very detailed, which, if at any moment establishes a position which is critical of religious discourse, it does so because it seeks to be consistent with its own religious nature. This critical attitude and its consistency with the principles upheld seeks to recover the most valuable aspect of religion for the human condition, which makes it interesting and challenging for these times.